Non-genetic Factors affecting Body Weight and Scrotal Circumference at First Semen Collection and Semen Production Traits of Kankrej Bulls - `Dangar, Nikhil S.; Brahmkshtri, Balkrishna P.; Pandya, Gaurav M.; Deshmukh, Niteen (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
This study was conducted on 13 bulls of Kankrej cattle breed maintained at Dama semen station of Banas dairy (Gujarat) to study the effects of non-genetic factors, viz., season of birth and year of birth on body weight at first semen collection (BWFSC) and scrotal circumference at first semen collection (SCFSC) as well as the effect of BWFSC and SCFSC on future semen production traits like semen production period, age of bull at disposal and lifetime production of frozen semen doses per bull. The overall least squares means for body weight of bulls and scrotal circumference of bulls at first semen collection, semen production period, age of bull at disposal and lifetime production of frozen semen doses per bull were 578.68 ± 25.18 kg, 30.86 ± 1.60 cm, 704.3 ± 151.22 days, 1875.73 ± 135.95 days and 55243.83 ± 21307.60 doses, respectively. Results of the present study revealed that body weight and scrotal circumference of bulls at first semen collection were not significantly affected by season of birth and year of birth. Similarly, BWFSC and SCFSC had no significant effect on semen production traits